О модификации вычислительного алгоритма решения задачи оптимального корректирования проектной железнодорожной линии - Билецкий, В.И. (Теорія оптимальних рішень, 2007)
The paper states a general problem conserned with correcting main parameters of project line of a railroad. An algorithm is described that is used to solve partial CMPPL problems with a specific schemes of choice of step-by-step advenced versions. Its advantages are pointed to when problems are solved in the operation mode.